1991
DOI: 10.1097/00006123-199103000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic schwannoma and epidermoid cyst occurring as a single cerebellopontine angle mass

Abstract: The case of a 66-year-old man with a 3-year progressive hearing loss and a homogeneous left cerebellopontine angle mass on magnetic resonance imaging scan is described. At surgery, the major portion of the mass was a typical encapsulated, solid, acoustic schwannoma, but the most rostral portion was a distinct, flaky, cystic mass without a well-defined capsule, typical of an epidermoid cyst. The radiographic and operative findings of this unique coexistence of two different benign cerebellopontine angle masses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
10
1
Order By: Relevance
“…4) The difference between our present case and the previous two cases 4,5) was that we could observe the second tumor, vestibular schwannoma. The previous two patients presented with symptoms of 7th and 8th cranial nerve disturbance, and the coexisting tumors were found during surgery.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…4) The difference between our present case and the previous two cases 4,5) was that we could observe the second tumor, vestibular schwannoma. The previous two patients presented with symptoms of 7th and 8th cranial nerve disturbance, and the coexisting tumors were found during surgery.…”
Section: Discussioncontrasting
confidence: 69%
“…2,8) Collision tumors in this area are rare, with only 15 reported cases: 7 cases of metastatic tumor and vestibular schwannoma, 2 cases of meningioma and vestibular schwannoma, 2 cases of vestibular schwannoma and epidermoid, 1 case of trigeminal schwannoma and epidermoid cyst, 1 case of trochlear and abducens nerve schwannoma and meningioma, 1 case of choroid plexus papilloma and vestibular schwannoma, 1 case of epidermoid and glioblastoma, and 1 case of vestibular schwannoma and cholesterol granuloma. 1,[3][4][5][7][8][9]11,12) The coexistence of schwannoma with intracranial epidermoid cyst as a distinct tumor mass has been reported only once. 11) Collision tumors of these types forming a single cerebellopontine mass are also rare, with only 2 cases of collision primary tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been two reported cases of a vestibular schwannoma coexisting with an epidermoid cyst as a single cerebellopontine angle mass. [1,2] Saito et al reported development of a vestibular schwannoma in a patient many years after excision of a cerebellopontine angle epidermoid. [3] This is the fourth such case of a vestibular schwannoma growing adjacent to an epidermoid tumor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that vestibular schwannomas seem to carry diverse genetic anomalies, specifically in cases of neurofibromatosis, with the patients usually presenting symptoms after the age of 30, coursing most commonly with the known triad of sensorineural hearing loss, tinnitus and balance difficulties. 3 However, it seems that epidermoid cysts arise during the intrauterine development, and they are believed to originate from epidermal inclusions during the formation of the second cerebral vesicle. The described incidence of vestibular schwannomas is of approximately 1.5/100.000 people, accounting for 7-10% of all primary intracranial tumors.…”
Section: Introductionmentioning
confidence: 99%